Islamic liberation theology: resisting the empire - Dabashi, Hamid (Routledge, 2008)
This book is a radical piece of counter-intuitive thinking on the clash of civilizations theory and global politics. The author argues that after 9/11 we have not seen a new phase in a long running confrontation between Islam and the West, but that such cataegories have collapsed. The West is no longer a unified actor and Islam is ideologically exhausted in its confontation with colonialism. Rather we are seeing the emergence of the US as a lone superpower, and a confrontation between a form of imperial globalized capital and a new Islamic theodicy.